PENGARUH TIME BUDGET PRESSURE, RISIKO KESALAHAN AUDIT, DAN MASA PERIKATAN AUDIT TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI DAERAH BALI - Pratama, I Made Indra; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi, 2015)
This study analyzed the effect of time budget pressure, the risk of error and the audit engagement audit to audit quality. The samples used were the auditors who worked on KAP in Bali. The number of auditors who became the study sample was 83 auditors from 9 Public Accounting Firm in Bali. The sampling method used was non-probability sampling, data processing method used is multiple linear regression. The analysis showed that the time budget pressure, the risk of error audits, and the audit engagement impact on audit quality. The results of the adjusted R-square is 0.615 which means that 61.5 percent of the variation of audit quality is affected by the model established time budget pressure, the risk of error audits, and the audit engagement. Mean of 38.5 percent is explained by other things that are not described in this study.
Keywords: Quality of audit, Public Accounting Firm